1987
DOI: 10.1016/0360-3016(87)90170-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tumor colony definition on ionizing radiation survival curves of melanoma-colony forming cells

Abstract: Definition of survival and measurement of colony size in soft agar assays is important in establishing in vitro radiation survival curves. Conventionally, survival is assessed according to colony-forming ability. The distinction between small colonies that are abortive and those that are viable often involves a difficult and arbitrary choice for the investigator. We have examined the effect of different minimum colony sizes (greater than or equal to 25, greater than or equal to 50, greater than or equal to 75,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Metastatic melanoma cell strains (c81-46A and c83-2c) were cultured in F-10 with 5% FCS, 5% calf serum, 1% glutamine, 100 units/mL penicillin, and 0.1 mg/mL streptomycin and designated as melanoma complete medium. Cell strains c81-46A and c83-2c have been described previously and were initially cloned through soft agar and will form tumors in nude mice (25). The passage number for the various cell strains used in these experiments was <8.…”
Section: Methodsmentioning
confidence: 99%
“…Metastatic melanoma cell strains (c81-46A and c83-2c) were cultured in F-10 with 5% FCS, 5% calf serum, 1% glutamine, 100 units/mL penicillin, and 0.1 mg/mL streptomycin and designated as melanoma complete medium. Cell strains c81-46A and c83-2c have been described previously and were initially cloned through soft agar and will form tumors in nude mice (25). The passage number for the various cell strains used in these experiments was <8.…”
Section: Methodsmentioning
confidence: 99%
“…Metastatic melanoma cell strains (c81-46A and c83-2c) were cultured in F-10 with 5% fetal calf serum, 5% calf serum, 1% glutamine, penicillin (100 units/ml), and streptomycin (0.1 mg /ml) and designated as melanoma complete medium. Cell strains c81-46A and c83-2c have been described previously and were initially cloned through soft agar and will form tumors in nude mice (Yohem et al, 1987). The passage number for the various cell strains used in these experiments was Ͻ8.…”
Section: Methodsmentioning
confidence: 99%
“…to decide which clones are to be counted as survivors. It has been shown that different clone-size cut-offs influences the results in clonogenic assays (Refs 55 57 ).…”
Section: Clonogenic Assaysmentioning
confidence: 99%